Neuropathic pain in cancer patients treated with bortezomib - S. Expósito Vizcaíno; J. Casanova-Mollà; L. Escoda; S. Galán; J. Miró (Neurología (English Edition), 2018)
Introduction: The neuropathic pain is the most habitual problem in the neuropathy induced by chemotherapy (NIQ) and the one that more interferes in the quality of life of the patients. His precocious detection turns out to be fundamental to reduce or to eliminate the problems that from this one stem. The aims of this study were: 1) determine the incident and NIQ's characteristics and neuropathic pain in patients with mieloma multiple (MM) treated with bortezomib, and 2) to evaluate the impact of the neuropathic pain in the activities of the daily life (AVD). Method: All the patients diagnosed of MM candidates for treatment with bortezomib attended in the Hospital Joan XXIII during 2013, took part. The participants were interviewed individually and were reporting on the presence, the characteristics and the impact of the pain, as well as of the adverse effects of the bortezomib. Results: There took part 22 persons, of which NIQ presented the half, being the degree 2 the predominant one. The most habitual location of the neuropathic pain was hands and feet; it was appearing in a spontaneous and progressive way deteriorating in rest and during the night, with predominance of positive symptoms. The impact of the pain was reflected in all the AVD. The principal limitation was the disability to enjoy the life. The peripheral neuropathy occupied the first place in order of subjective importance for the patient followed by the fatigue and the constipation. Conclusions: A proper assessment and early detection of neuropathic pain is critical to minimising its impact on the quality of life of patients. Resumen: Introducción: El dolor neuropático es el problema más habitual en la neuropatía inducida por quimioterapia (NIQ) y el que más interfiere en la calidad de vida de los pacientes. Su detección precoz resulta fundamental para reducir o eliminar los problemas que de este se derivan. Los objetivos de este estudio eran: 1) determinar la incidencia y las características de NIQ y dolor neuropático en pacientes con mieloma múltiple (MM) tratados con bortezomib, y 2) evaluar el impacto del dolor neuropático en las actividades de la vida diaria (AVD). Método: Todos los pacientes diagnosticados de MM candidatos a tratamiento con bortezomib atendidos en el Hospital Joan XXIII durante 2013, participaron. Los participantes eran entrevistados individualmente e informaban sobre la presencia, las características y el impacto del dolor, así como de los efectos adversos del bortezomib. Resultados: Participaron 22 personas, de las cuales la mitad presentaron NIQ, siendo el grado 2 el predominante. La localización más habitual del dolor neuropático era manos y pies; aparecía de manera espontánea y progresiva empeorando en reposo y durante la noche, con predominio de síntomas positivos. El impacto del dolor se reflejó en todas las AVD. La limitación principal fue la incapacidad para disfrutar de la vida. La neuropatía periférica ocupó el primer lugar en orden de importancia subjetiva para el paciente seguido de la fatiga y el estreñimiento. Conclusiones: Una adecuada evaluación y detección precoz del dolor neuropático es fundamental para minimizar su impacto en la calidad de vida del paciente. Keywords: Pain, Peripheral neuropathy, Bortezomib, Multiple myeloma, Early detection, Effects on activities of daily living, Palabras clave: Dolor, Neuropatía periférica, Bortezomib, Mieloma múltiple, Detección precoz, Repercusiones en las Actividades de la vida diaria